Pendidikan Agama Islam Berbasis Reward and Punishment untuk Penguatan Motivasi Belajar Siswa di Sma Islam - Gesang Mulya Uga Wicaksana; Muh. Hanif (STIKes Ibnu Sina Ajibarang, 2026)
This qualitative study aims to explore the effectiveness of reward-and-punishment-based Islamic Religious Education in strengthening students' learning motivation at SMA Negeri 1 Bukateja using Travis Hirschi's social control theory framework. This research was conducted through a case study approach in one of the public high schools in Purbalingga Regency. Data were collected through interviews, participant observation, and documentation studies. The results of the study indicate that the implementation of rewards and punishments functions as a social control mechanism that is able to activate four elements of social bonds: attachment, commitment, involvement, and trust. The reward system in the form of praise, certificates, and gifts has been proven to strengthen the emotional bond between students and teachers, thereby increasing active participation and enthusiasm for learning. Meanwhile, educational punishments, such as reprimands, additional assignments, and community service, are able to build student commitment to rules and reduce indiscipline behavior.This study contributes to the development of Islamic education theory through a social control perspective and serves as a practical reference for Islamic Religious Education teachers in designing effective, fair, and sustainable learning systems.